Electron Transport Studies In 12-mer Single Strand Dna Oligomers By Muon Spetroscopy And Scanning Tunneling Microscopy - Rozak, Harison (2021)
The aims of this study are to determine which of the four samples of 12-mer single-strand: adenine, cytosine, guanine, and thymine (ssA12, ssC12, ssG12, and ssT12) is the most and least conductive. Besides, to find out the behaviour of the electron transfer in these samples. Scanning tunneling microscope (STM) and muon spin relaxation (μSR) measurements were performed to achieve the objectives study. The STM technique was also used to determine the shape of each oligomer sample and to study the influence of environmental conditions on the conductivity measurement. From STM measurements, each base in DNA was found to be conductive, and the most conductive base is ssG12. The sequence of conductivity based on the tip-height profile (Hp) measurement is ssG12 > ssC12 > ssA12 > ssT12. The shapes of oligomers were observed to be different from each other because ssDNA12 samples (ssA12, ssC12, ssG12, and ssT12) are flexible structures as they are formed without any complement bases and strand. These oligomers were also seen aligned in parallel from each other and formed a one-dimensional (1D) chain structure. The μSR technique successfully detected the existence of electron transfer in ssDNA12. The behaviour of the electron transfer along the ssDNA12 was suggested in quasi-1D at room temperature. From conductivity measurement in different environment conditions on ssG12, it was found that conductivity did not depend on the environmental conditions. Overall, it can be suggested that ssDNA12 itself is conductive and they can be a medium for the electron to transfer